Mixed signals? Morphological and molecular evidence suggest a color polymorphism in some neotropical polythore damselflies. - Melissa Sánchez Herrera; William R Kuhn; Maria Olalla Lorenzo-Carballa; Kathleen M Harding; Nikole Ankrom; Thomas N Sherratt; Joachim Hoffmann; Hans Van Gossum; Jessica L Ware; Adolfo Cordero-Rivera; Christopher D Beatty (PLoS ONE, 2015)
The study of color polymorphisms (CP) has provided profound insights into the maintenance of genetic variation in natural populations. We here offer the first evidence for an elaborate wing polymorphism in the Neotropical damselfly genus Polythore, which consists of 21 described species, distributed along the eastern slopes of the Andes in South America. These damselflies display highly complex wing colors and patterning, incorporating black, white, yellow, and orange in multiple wing bands. Wing colors, along with some components of the male genitalia, have been the primary characters used in species description; few other morphological traits vary within the group, and so there are few useful diagnostic characters. Previous research has indicated the possibility of a cryptic species existing in P. procera in Colombia, despite there being no significant differences in wing color and pattern between the populations of the two putative species. Here we analyze the complexity and diversity of wing color patterns of individuals from five described Polythore species in the Central Amazon Basin of Peru using a novel suite of morphological analyses to quantify wing color and pattern: geometric morphometrics, chromaticity analysis, and Gabor wavelet transformation. We then test whether these color patterns are good predictors of species by recovering the phylogenetic relationships among the 5 species using the barcode gene (COI). Our results suggest that, while highly distinct and discrete wing patterns exist in Polythore, these "wingforms" do not represent monophyletic clades in the recovered topology. The wingforms identified as P. victoria and P. ornata are both involved in a polymorphism with P. neopicta; also, cryptic speciation may have taking place among individuals with the P. victoria wingform. Only P. aurora and P. spateri represent monophyletic species with a single wingform in our molecular phylogeny. We discuss the implications of this polymorphism, and the potential evolutionary mechanisms that could maintain it.